2005
DOI: 10.1897/04-266r.1
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and tissue‐specific distribution of selected polychlorinated biphenyls in developing chicken embryos

Abstract: Fertilized chicken eggs were injected with high doses of individual polychlorinated biphenyl (PCB) congeners (0.5 microg of PCB 77, 9.8 microg of PCB 153, or 10.9 microg of PCB 180) before incubation to investigate the structure-specific uptake of these compounds by the embryo and their accumulation in brain and liver tissue. In accordance with earlier publications, a gradual uptake and accumulation of these compounds was observed during the last week of embryonic development. The PCB uptake and distribution t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 36 publications
5
14
0
Order By: Relevance
“…Collectively, these studies indicate that PCBs, like other compounds present in yolk, are absorbed slowly in the first half of incubation, with more rapid use later in development. The proportion of PCB reaching the chicken embryo changed from 2% at embryonic day 13 to 18% at embryonic day 19 [60] and 0.8% at embryonic day 13 to 15% at embryonic day 18 [68]. This is in accordance with yolk and albumen usage by developing embryos.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Collectively, these studies indicate that PCBs, like other compounds present in yolk, are absorbed slowly in the first half of incubation, with more rapid use later in development. The proportion of PCB reaching the chicken embryo changed from 2% at embryonic day 13 to 18% at embryonic day 19 [60] and 0.8% at embryonic day 13 to 15% at embryonic day 18 [68]. This is in accordance with yolk and albumen usage by developing embryos.…”
Section: Discussionsupporting
confidence: 66%
“…Injections of PCBs showed increases in absorption by the embryo during development [66][67][68][69]. However, the distribution and uptake of PCBs following air cell and albumen injections have not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The brain is mainly made up of polar phospholipids and sphingolipids whereas it has only a minor portion of triglycerides in contrast with other tissues. In an exposure experiment with chicken embryos, Maervoet et al (2005) found that concentrations of PCBs (PCB 77,153 and 180) remained relatively stable in the brain at the latest stage before hatching, while the levels increased exponentially in other tissues such as the liver. Considering that the BBB was still incomplete at that time (the BBB is only fully completed after hatching), the same study concluded that the specific lipid composition of the brain is less attractive for lipophilic compounds such as PCBs and thus responsible for the lower concentrations of PCBs found in the brain.…”
Section: Blood/brain Partition Coefficientsmentioning
confidence: 99%
“…The AhR-ARNT heterodimer activates transcription of target genes including CYP1A1 which is considered to be the most sensitive biomarker of exposure to TCDD and dioxin-like compounds (Sorg, 2014;Yasui et al, 2007). The non-coplanar PCBs, which are the most abundant in the environment, constitute a large part of the PCB residue detected in animal tissues and have been reported to accumulate preferentially in several tissues (Gregoraszczuk et al, 2003;Maervoet et al, 2005). It has been found that this class of PCBs is a ligand for estrogen receptors (Bonnefeld-Jorgensen et al, 2001).…”
Section: Introductionmentioning
confidence: 99%